Association between circulating resistin levels and thyroid dysfunction: A systematic review and meta-analysis - Zhou, Lin; Song, Kang; Luo, Wei (Frontiers in Endocrinology, 2023)
Abstract Background: As a product of adipose tissue, resistin exceeds other adipokines in its role in regulating appetite, energy expenditure, insulin sensitivity, inflammation, and immunity, similar to thyroid hormones. This study aimed to evaluate the association between resistin levels and thyroid dysfunction and to explore variations in circulating resistin levels before and after treatment for thyroid dysfunction. Methods: This study was conducted according to the Preferred Reporting Items for Systematic Review and Meta-Analysis statement. A comprehensive search of PubMed, Embase, and Cochrane databases was conducted until June 15, 2022, with no start date restriction, according to the preregistered protocol (PROSPERO-CRD42022336617). RevMan version 5.4 and R software package version 4.2.0 were used for statistical analyses. Results: Fourteen studies with 1716 participants were included in this study. The findings of the meta-analysis confirmed that the resistin levels of patients with thyroid dysfunction were significantly higher than those of the euthyroid function control group (mean difference [MD] = 2.11, 95% confidence interval [CI] = 1.11–3.11, P < 0.00001). Furthermore, the resistin levels of patients with hyperthyroidism (MD = 3.23, 95% CI = 0.68–5.79, P = 0.01) and subclinical hypoidism (MD = 1.37, 95% CI = 0.31–2.42, P = 0.01) were significantly higher than those of euthyroid controls. The resistin levels of patients with thyroid dysfunction after treatment were significantly lower than those before treatment (MD = 1.00, 95% CI = 0.34–1.65, P = 0.003), especially in patients with hyperthyroidism (MD = 2.16, 95% CI = 1.00–3.32, P = 0.0003). Correlation analysis confirmed a positive correlation between resistin levels and free triiodothyronine (FT3) levels in patients with thyroid dysfunction (r = 0.27578, P = 0.001). Conclusions: Our meta-analysis demonstrates that resistin levels are significantly higher in patients with thyroid dysfunction, and the resistin levels after treatment in patients with thyroid dysfunction are significantly lower than those before treatment. Correlation analysis shows a positive correlation between resistin levels and FT3 levels in patients with thyroid dysfunction.